Protective Effects of Appropriate Amount of Nuts Intake on Childhood Blood Pressure Level: A Cross-Sectional Study - Feng, Ye; Bi, Yang; Tang, Xian; Zhang, Ping; Tong, Jishuang; Peng, Xin; Tian, Jie; Liang, Xiaohua (Frontiers in Medicine, 2022)
Objective Increased blood pressure (BP) is a major risk factor for cardiovascular disease (CVD) in adults. Regular consumption of nuts may improve some BP in adults whereas evidence in children is relatively lacking. This study aimed to determine the efficacy of nuts intake on BP in children. Methods Stratified cluster sampling was performed to include a total of 15,268 primary school children aged 6–12 years in urban and rural areas in Southwest China. The daily nuts intake dosage was collected by questionnaires, and generalized linear model (GLM) and logistic regression were used to analyze the relationship between nuts intake and BP. Results For the total subjects, 11,130 (72.9%) participants consumed <35 g/day of nuts, 1,145 (7.5%) participants consumed 35 g/day ≤ nut <50 g/day of nuts, 2,053 (13.4%) participants consumed 50~100 g/day of nuts, and 940 (6.2%) participants consumed over 100 g/day of nut. For sex subgroup, 1,074 (13.53%) boys and 979 (13.35%) girls consumed 50~100 g/day of nuts. Compared with the 50~100 g/day of nuts intake group, systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were significantly different in <35 g/day, 35g/day ≤ nut <50 g/day, and >100 g/day nuts intake groups (all p < 0.001). The logistic regression showed that compared with the 50~100 g/day group, the other three groups are more likely associated with childhood hypertension (all p < 0.001). Therefore, a U-shaped relationship between nuts intake and BP level was identified. Conclusions The finding suggests that intake of 50~100 g/day nuts is the recommended dose of nuts intake to control childhood hypertension, as well as for cardioprotection purposes.